Cyberculture in Cyberlife (Description of Travel Influencer Interactions with Their Followers on Instagram) - Candraningrum, Diah Ayu (Jurnal Komunikasi, 2023)
The tourism industry in Indonesia has been growing rapidly for a long time. Although the pandemic Covid-19 has passed now, the presence of social media influencers (SMI) in the tourism sector still exists because their existence is considered effective in promoting Indonesian tourism. They can discuss travel activities, tourist destinations or just give appreciation through emojis in the comment space. Therefore, the purpose of this study is to describe the interactions that occur between different SMI characters and their followers through posts and comments uploaded on Instagram from January to March 2023. This period was chosen because it was the momentum of the revival of Indonesian tourism after the pandemic. The research approach used is qualitative with a virtual ethnography research method, with data collection techniques in the form of observation and online data collection. The data analysis techniques used are: 1) Elicitation stage which is the collection of raw data; 2) Reduction stage which consists of 3 stages, namely: Selection-Coding-Clustering; and 3) Visualization stage. Data collection of comments was carried out using the IGCommentExporter program, meanwhile data analysis conducted by Voyant Tools program. Furthermore, the discussion themes that emerged from the findings will be discussed with the concept of Cyberculture that has been discussed previously. The unit of analysis used in this research is the text message in the comment section of the Instagram accounts of two top female travel influencers in Indonesia @medinakamil and @puanindya. By using the concept of Cyberculture, this research concludes that the interaction that occurs between travel influencers and their followers is based on the followers' interest in the influencer's figure itself and also the online friendliness that displays in the comments column.